# Tutor profile: Rashelle B.

## Questions

### Subject: Pre-Calculus

You've decided you want a plant for your room. At the gardening store, There are 4 different plants (tulip, roses, ficus, fern) and 4 different kinds of pots to hold the plant (clay, plastic, metal, and wood). If you randomly pick a plant and pot, what is the probability that you'll end up with a tulip in a wood pot?

The equation for probability is favorable combinations/total possible combinations. First, we need to know how many total possibilities are there. We have 4 plants and 4 pots. 4x4=16, so we have 16 total possible outcomes that are equally likely to happen. Second, we need to figure out how many favorable combinations we have. We want to know the probability of getting a tulip in a wood pot. There are only 1 tulip and 1 wood pot. 1x1=1, so we have 1 favorable combination. Third, we plug in the numbers we got for favorable outcomes and total possible combinations into our probability equation. We have 1 favorable outcome and 16 possible combinations. So the probability of ending up with a tulip in a wood pot is 1/16.

### Subject: Pre-Algebra

What is the volume of a rectangular prism that has a width of 3 in, length of 6 in, and a height of 4 in?

The volume of a rectangular prism is length x width x height. So for this problem, we would multiply the length of 6 in by the width of 3 in by the height 4 in. Since our unit of measurement in inches and we multiplied it 3 times, we will end up with in^3 Volume=6inx3inx4in=72in^3.

### Subject: Algebra

Evaluate f(2)-f(1), given f(x)=6x+1.

First, we will work with the first part of the equation f(2)-f(1), which is f(2). If f(x)=6x+1 than f(2)=6(2)+1. Because of the order of operations, you'll do 6(2) first. 6(2)=12. So now we have f(2)=12+1=13. Next, we will work with the second part of the equation f(2)-f(1), which is f(1). If f(x)=6x+1 than f(1)=6(1)+1. Because of the order of operations, you'll do 6(1) first. 6(1)=6. So now f(1)=6+1. Next, we take the answers we got which were f(2)=13 and f(1)=7 and plug them into our original equation of f(2)-f(1). f(2)-f(1)-13-7=6. So the answer is 6.

## Contact tutor

needs and Rashelle will reply soon.